2011
DOI: 10.1016/j.biomaterials.2010.11.071
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biophysical attributes of the ocular trabecular meshwork associated with glaucoma on the cell response to therapeutic agents

Abstract: Glaucoma is a devastating neurodegenerative disease, which can lead to vision loss and is associated with irreversible damage to retinal ganglion cells. Although the mechanism of disease onset remains unknown, we have recently demonstrated that the stiffness of the ocular trabecular meshwork (HTM) increases dramatically in human donor eyes with a history of glaucoma. Here we report that polyacrylamide hydrogels, which mimic the compliant conditions of normal and glaucomatous HTM, profoundly modulate cytoskelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 46 publications
9
108
0
2
Order By: Relevance
“…Published protocols were followed to make polyacrylamide gels composed of 8% (wt/vol) acrylamide, 3% (wt/vol) (3-acrylamidepropyl) trimethylammonium chloride (API), and a variable percentage of bisacrylamide (0.04, 0.1, 0.2, 0.5, and 1.3%; wt/vol) (18,(35)(36)(37). These API gels were positively charged and electrostatically absorb ECM proteins, including collagen 1 (36).…”
Section: Methodsmentioning
confidence: 99%
“…Published protocols were followed to make polyacrylamide gels composed of 8% (wt/vol) acrylamide, 3% (wt/vol) (3-acrylamidepropyl) trimethylammonium chloride (API), and a variable percentage of bisacrylamide (0.04, 0.1, 0.2, 0.5, and 1.3%; wt/vol) (18,(35)(36)(37). These API gels were positively charged and electrostatically absorb ECM proteins, including collagen 1 (36).…”
Section: Methodsmentioning
confidence: 99%
“…At the micro-to nanoscopic level, bulk and local compliance influence a wide menu of fundamental cell behaviors, including cell morphology, [14][15][16][17] proliferation, 16,[18][19][20] motility, 15,[21][22][23][24][25] differentiation, 18,[26][27][28][29] and response to therapeutic agents. 30 It is therefore important to properly characterize the compliant biophysical state of tissues to understand how this biophysical attribute relates to proper function. However, a cursory review of the literature quickly reveals significant differences in reported values of the compliance of soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies from our laboratory [8][9][10][11] and others [12][13][14][15][16][17][18][19] have demonstrated that modulation of substratum stiffness can alter phenotypic characteristics of cells, gene expression, or response to drugs. However, the primary molecular mechanisms by which the biophysical attributes influence cell behaviors remain unknown.…”
mentioning
confidence: 99%